RACISM IN TERRY GEORGE’S MOVIE HOTEL RWANDA - Kurniati Delima Sinaga; Amrin Saragih; Syamsul Bahri (LINGUISTICA, 2020)
The title of this thesis is Racism in Terry George’s Movie Hotel Rwanda. This study is aimed to analyze what kinds of Hutu’s oppressions occurred in the movie, and what are linguistically realized toward racism. The writer applies the theories from Iris Marion Young about oppression in black America society (1990).Based on its form, Young was divided oppression into 5 types, they are (1) exploitation, (2) marginalization,(3)powerlessness, (4) culture imperialism, and (5) violence. Racism is a belief or doctrine that inherent differences among the various human races determine cultural or individual achievement. Oppression is when a person or group in a position of power controls the powerless in cruel and unfair ways. The writer focuses on the analysis of oppression based on Hotel Rwanda script, and finally oppression is found as the most dominant thing that the depict racism in the movie.. Keywords: oppression, racism